Shedding Light on Microbial “Dark Matter”: Insights Into Novel Cloacimonadota and Omnitrophota From an Antarctic Lake - Williams, Timothy J.; Allen, Michelle A.; Berengut, Jonathan F.; Cavicchioli, Ricardo (Frontiers in Microbiology, 2021)
The potential metabolism and ecological roles of many microbial taxa remain unknown because insufficient genomic data are available to assess their functional potential. Two such microbial ‘dark matter’ taxa are the Candidatus bacterial phyla Cloacimonadota and Omnitrophota, both of which have been identified in global anoxic, organic-carbon-rich environments. Using 24 metagenome assembled genomes (MAGs) obtained from an Antarctic lake (Ace Lake, Vestfold Hills), novel lineages and novel metabolic traits were identified for both phyla. The Cloacimonadota MAGs exhibited a capacity for carbon fixation using the reverse tricarboxylic acid cycle driven by oxidation of hydrogen and sulfur. Certain Cloacimonadota MAGs encoded proteins with dockerin and cohesin domains consistent with the assembly of an extracellular cellulosome-like structure used for degradation of polypeptides and polysaccharides. The Omnitrophota MAGs represented phylogenetically diverse taxa that were predicted to possess a strong biosynthetic capacity for amino acids, nucleosides, fatty acids, and essential cofactors. All of the Omnitrophota were inferred to be obligate fermentative heterotrophs that utilize a relatively narrow range of organic compounds, have an incomplete tricarboxylic acid cycle, and possess a single hydrogenase gene important for achieving redox balance in the cell. We reason that both Cloacimonadota and Omnitrophota form syntrophic interactions with hydrogen-consuming partners (methanogens and Desulfobacterota, respectively) and therefore occupy specific niches in Ace Lake. By extension, we envisage that Cloacimonadota and Omnitrophota elsewhere in the world exist in association with hydrogenotrophic partners